P4. Lateralisation of delta band activity in the MEG in patients with focal epilepsy and its relation to verbal fluency. Issue 8 (August 2021) - Schuster, A.M.; Behrens, M.; Conradi, N.; Strzelczyk, A.; Rosenow, F.; Rampp, S.; Merkel, N.
Abstract : Introduction Lateralised changes in neuronal activity, as recorded with magnetoencephalography (MEG), are known to indicate the epileptogenic hemisphere in patients with focal epilepsy. Besides interictal spikes, regional slowing of background activity into the delta band (1–4 Hz) seems to offer lateralisation clues, as it is pathological in awake state and considered as a sign of dysfunction [1]. We thus investigated delta power and its hemispheric occurrence in patients with left and right focal epilepsy as well as healthy controls. We further evaluated the correlation between delta power and verbal fluency to estimate the interrelation between slowing and cognitive functioning. Method Resting state MEG was recorded from 26 patients with left ( n = 15) and right ( n = 11) focal epilepsy as well as 10 healthy controls. Focal epilepsy diagnosis and the side of the epileptogenic focus were determined during video-EEG-monitoring. Data was analysed using Matlab [2] and the Matlab Toolbox Fieldtrip [3] regarding hemispheric group differences in absolute delta power. Using non-parametric tests, we compared delta power between (1) epilepsy patients and healthy controls, (2) patients with left and right focal epilepsy, and (3) the hemispheres within patients with left and right focal epilepsy. Spearman's rank correlations between delta power and semantic as well as phonemic verbal fluency were evaluated. Results We found that (1) compared to healthy controls, patients with focal epilepsy showed higher delta power in the hemisphere ipsilateral ( p = .027) and contralateral to the epileptogenic focus ( p = .037). (2) Patients with left and right focal epilepsy did not differ in either of the hemispheres. (3) Patients with right focal epilepsy showed higher delta power in the ipsilateral-to-focus right than the contralateral-to-focus left hemisphere ( p = .016). Patients with left focal epilepsy did not show a significant difference between the hemispheres. Lastly, we found a significant negative Spearman's rank correlation between delta power and phonemic verbal fluency ( rs = −0.59, p = .008), but not between delta power and semantic verbal fluency. Discussion Our findings suggest that delta band activity does not only occur as lateralised pathologic change in neuronal activity, but rather can be detected in the non-epileptogenic hemisphere as well. Differences in the correlation of semantic and phonemic verbal fluency with delta power suggest that delta band activity might be less relevant for language functions but could rather indicate executive dysfunction. These results have to be confirmed and further analysed in a larger sample of patients with focal epilepsy. [1] Lin, Y. et al. (2018). Front. Neurol. doi: 10.3389/fneur.2018.00829 [2] The MathWorks, Inc. MATLAB . Version 2019b [3] Oostenveld, R. et al. (2011). Comput Intell Neurosci . doi: 10.1155/2011/156869